A New Challenging Strategy in the Prevention and Management of Tumor Lysis Syndrome in Patients with Chemo-Sensitive Hematological Malignancies. (19th May 2019) - ELJack, Ammar; El Abdallah, Mohamad; Al-Banaa, Kadhim; Chaudhry, Kashif; Musa, Faisal
Abstract : Introduction . Tumor lysis syndrome (TLS) is a metabolic derangement that results from rapid destruction of cells. It happens frequently in cancers receiving chemotherapy, particularly hematological malignancies. It can lead to death in severe cases. Tumor lysis syndrome that leads to acute renal failure requiring dialysis and/or ICU admission can be associated with a higher rate of complications and mortality. Case Report . We present a 24-year-old male patient with Burkitt's lymphoma. After receiving one cycle therapy, he developed severe kidney injury from TLS. We initiated renal replacement therapy soon after his admission to the ICU, with marked response to therapy. This led to early discharge from the ICU. Conclusion . Early initiation of renal replacement therapy after TLS-AKI can improve the severity of AKI and hasten recovery and prevent complications. This can lead to earlier discharge from the hospital and better outcomes.